Storing, searching and dissemination of chemical information - Zielesny, Achim (Henry Stewart Talks, 2011)
Sequential data search, Bisection with sorted data, Data structure binary tree & hash table, Speed vs. Optimum structure, Problems of hash methods, Matching of data, Index creation, Chemical exact structure and substructure search, Brute-force explanation, ABAS in practice, Heuristic backtracking in molecular tree, The concept of screening, Tanimoto coefficient, Chemical reaction retrieval, Atom-to-atom mapping, Breaking/Formation of bonds, Super atoms, generic groups, R groups, Generation of synthesis trees for synthesis, Document and fact retrieval, Exact & Partial match searches, Similarity & Associative searches
Reviewed at 2022/04/12